2009
DOI: 10.1111/j.1460-9568.2009.06872.x
|View full text |Cite
|
Sign up to set email alerts
|

Tonically active neurons in the striatum differentiate between delivery and omission of expected reward in a probabilistic task context

Abstract: Tonically active neurons (TANs) in the primate striatum are responsive to rewarding stimuli and they are thought to be involved in the storage of stimulus-reward associations or habits. However, it is unclear whether these neurons may signal the difference between the prediction of reward and its actual outcome as a possible neuronal correlate of reward prediction errors at the striatal level. To address this question, we studied the activity of TANs from three monkeys trained in a classical conditioning task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 42 publications
9
78
3
2
Order By: Relevance
“…In our previous study, we showed that some TANs responded to reward and no reward with decreases and increases in firing, respectively (Apicella et al, 2009). These opposite response patterns may reflect positive and negative errors in prediction of reward, consistent with the rules of temporal difference models of associative learning (Schultz et al, 1997;Dayan and Balleine, 2002;Montague and Berns, 2002).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…In our previous study, we showed that some TANs responded to reward and no reward with decreases and increases in firing, respectively (Apicella et al, 2009). These opposite response patterns may reflect positive and negative errors in prediction of reward, consistent with the rules of temporal difference models of associative learning (Schultz et al, 1997;Dayan and Balleine, 2002;Montague and Berns, 2002).…”
Section: Introductionmentioning
confidence: 83%
“…For each neuron, a normalized perievent time histogram was obtained by dividing the content of each bin by the number of trials, and the population histogram was constructed by averaging all normalized histograms. We also used a time-window analysis to statistically assess and compare changes in the average population response between conditions (Apicella et al, 2009). First, latency and duration of these changes were determined for each population histogram.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, on the neuron level, there have recently been contradictory reports concerning the RPE coding in the striatum. Morris et al (2004) recorded the activity of TANs (tonically active neurons), or striatal cholinergic interneurons, in monkeys and concluded that TANs in monkeys do not code RPE, whereas Apicella et al (2009) have reported that they responded to RPE in a fashion inverse to that of dopamine neurons, that is, they show inhibitory activity for a positive RPE. Roesch et al (2009) recorded the activity of rat striatal neurons that were apparently medium spiny projection neurons and reported that only few of them appeared to code RPE signals, whereas Kim et al (2009) found both inverse and noninverse RPE coding in several medium spiny neurons and interneurons.…”
Section: Introductionmentioning
confidence: 99%